2018
DOI: 10.3390/catal8090363
|View full text |Cite
|
Sign up to set email alerts
|

High CO Methanation Performance of Two-Dimensional Ni/MgAl Layered Double Oxide with Enhanced Oxygen Vacancies via Flash Nanoprecipitation

Abstract: As a methanation tool, two-dimensional (2D) carrier-loaded Ni has attracted the attention of many researchers. We successfully prepared 2D MgAl layered double oxides (LDO) carriers via flash nanoprecipitation (FNP). Compared to the LDO samples prepared by conventional co-precipitation (CP), the 2D MgAl-LDO (FNP) has more oxygen vacancies and more exposed active sites. The Ni/MgAl-LDO (FNP) catalyst demonstrates a CO conversion of 97%, a CH 4 selectivity of 79.8%, a turnover frequency of 0.141 s −1 , and a CH 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…In Figure 6b, the O 1s spectra of Ni/SF-SiO 2 and Ni/SF-SiC catalysts could be distinguished into four sub-peaks: The weakly binding energy peaks (O I and O II ) were related to the surface lattice oxygen and the adsorbed oxygen [44], respectively; the higher binding energy (O III and O IV ) corresponded to the defects with a low oxygen coordination and the metal-oxygen bonds, respectively [45]. The binding energy of O 1s of Ni/SF-SiC was higher than Ni/SF-SiO 2 , demonstrating that the stronger metal-support interactions between Ni and SF-SiC [21].…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 6b, the O 1s spectra of Ni/SF-SiO 2 and Ni/SF-SiC catalysts could be distinguished into four sub-peaks: The weakly binding energy peaks (O I and O II ) were related to the surface lattice oxygen and the adsorbed oxygen [44], respectively; the higher binding energy (O III and O IV ) corresponded to the defects with a low oxygen coordination and the metal-oxygen bonds, respectively [45]. The binding energy of O 1s of Ni/SF-SiC was higher than Ni/SF-SiO 2 , demonstrating that the stronger metal-support interactions between Ni and SF-SiC [21].…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic peak of MgO periclase were observed at 2θ ≈ 37 , 43 and 63 in all samples. This indicated that the Mg-Al mixed oxide was formed after calcination process 23 . The distinguished peak of V and Mo species were not found in XRD patterns of modified catalysts.…”
Section: Catalyst Characterizationmentioning
confidence: 88%
“…Therefore, the syngas goes through a series of further transformations, such as two stages of water gas shift [9][10] and one of methanation [11] [12], preferential oxidation [13] or a treatment with permselective membranes [14]. The overall process is effective, but inefficient and not suitable for distributed production; where small and smart plants are needed.…”
Section: Introductionmentioning
confidence: 99%